The Bronchiectasis in Geriatric Patients: Adaptation of Diagnosis and Management in the Context of Advanced Age: A Case Report - Aulia, Khansa Tsabitah; Pratiwi, Prasetyaning Estu (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Introduction: Bronchiectasis is an abnormal and permanent dilation of the bronchi caused by chronic inflammatory processes or recurrent infections. This condition can aggravate the patient's respiratory status, especially if it is accompanied by complications. Case Description: A 70-year-old man came in with complaints of chronic cough with phlegm and increasingly severe shortness of breath. No history of tuberculosis or other systemic diseases was found. Thoracic photos and CT scans show a picture of bronchiectasis with honeycombing leading to pulmonary fibrosis. Laboratory tests showed leukocytosis, increased urea and creatinine, and impaired liver function. The patient received injectable moxifloxacin antibiotic therapy followed by oral ciprofloxacin, as well as other supportive therapies. Clinical improvement begins to be seen after a few days of treatment. Discussion: Bronchiectasis in the elderly is often a challenge due to symptoms that overlap with other lung diseases as well as the presence of comorbidities. The absence of a definitive cause in these patients led to the diagnosis of idiopathic bronchiectasis. The honeycombing findings on imaging indicate the possibility of pulmonary fibrosis aggravating the condition. Prompt and appropriate management is essential to prevent disease progression. Conclusions: Idiopathic bronchiectasis with complications of pulmonary fibrosis is a rare and challenging case in diagnosis and management. A thorough radiological and laboratory examination is helpful in establishing the diagnosis and determining the optimal therapy.